Cross-sectional study to evaluate the influence of nutritional behavior on the dental health of Romanian teen agers - Saveanu, Catalina Iulia; Păduraru , Cosmin-Gabriel; Anistoroaei, Daniela; Săveanu, Alexandra Ecaterina; Cretu , Cosmin Constantin; Golovcencu , Loredana; Armencia, Adina Oana; Bamboi, Irina (Progress in Nutrition, 2022)
Nutritional behavior is one of the current concerns regarding the primary prevention of carious lesions. Material and method: Cross-sectional study was performed for 150 subjects aged between 12-18 years randomly selected. The assessment of knowledge and attitudes about influence of nutritional behavior on the dental health was carried out by the method of the questionnaire for: general data, frequency of snacks, consumption of carbonated drinks with sugar and without sugar, consumption of sugar, sweeteners, sweets, fruits, dairy products, chewing gum. Also, dates about subjective symptoms regarding the appearance of gingival bleeding and the presence of pain in the form of dental sensitivity, were recorded. The dates were collected online and then entered into an IBM SPSS statistic26. The Chi-Square Test was applied taking into account the Pearson Chi-square and the level of significance was α=0.05. Results and Discussion: The comparison of the results regarding the consumption of carbonated drinks with sugar showed differences for class level, gingival bleeding and for dairy products p≤0.05 and increase the number of subjects with toothache in relation to frequency of meals r =.51. The frequency of fruit consumption is not different at the level of studies and is not closely correlated with the presence of gingival bleeding, the presence of pain or the consumption of dairy products. Only 26%(39) do not consume chewing gum and of those who consume only 22.7%(34) consume sugar-free chewing gum, and 12%(18) chewing gum with fluoride. Conclusion: Nutritional behavior is an important factor on which oro-dental health depends.